Serlo of Bayeux and England - Elisabeth Van Houts (Tabularia)
After a short introduction highlighting Serlo’s ambiguous attitude to the English and its king in 1105-1106, I shall discuss three texts which link Serlo with England. First there is Serlo’s poem Defensio pro filiis presbyterorum of which the oldest copy is preserved (incompletely) in a manuscript of Exeter Cathedral c. 1100 (Cambridge CCC ms 190, p. 361). The first 59 lines, in a haphazard order, have survived and concentrate mainly on the sacrament of baptism, the fact that sons cannot be held responsible for the sins of their fathers and the legislators’ lack of attention for simony and homosexuality. Second, I will discuss Serlo’s poem ad Murielem, the versificatrix nun of Wilton (d. before 1113) which was written after Baudri of Bourgueil’s poem for her. Thirdly and briefly I will explore the implications of the suggestion, first raised by Edoardo D’Angelo, that the poem Septem maiores numeramus was written by Serlo for Queen Edith Matilda (d. 1118), perhaps as a contribution to one of her competitions organised for poets.